2017
DOI: 10.1017/wet.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cover Crops on Management of Amaranthus Species in Glyphosate- and Glufosinate-Resistant Soybean

Abstract: A field study was conducted for the 2014 and 2015 growing season in Arkansas, Indiana, Illinois, Missouri, Ohio, and Tennessee to determine the effect of cereal rye and either oats, radish, or annual ryegrass on the control of Amaranthus spp. when integrated with comprehensive herbicide programs in glyphosate-resistant and glufosinate-resistant soybean. Amaranthus species included redroot pigweed, waterhemp, and Palmer amaranth. The two herbicide programs included were: a PRE residual herbicide followed by POS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
3
18
1
Order By: Relevance
“…Our results do not provide supporting evidence that surface residue mulch reduced herbicide efficacy or cash crop yields. Recent studies in corn and soybean production regions of the Midwest and Midsouth support the inference that herbicide inputs are the primary driver of cash crop yields and weed control performance, including multiple herbicide-resistant Amaranthus spp., when cover crops are integrated as a component of an IWM strategy (Loux et al 2017;Montgomery et al 2018;Wiggins et al 2015).…”
Section: Weed Control and Yield Performance Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results do not provide supporting evidence that surface residue mulch reduced herbicide efficacy or cash crop yields. Recent studies in corn and soybean production regions of the Midwest and Midsouth support the inference that herbicide inputs are the primary driver of cash crop yields and weed control performance, including multiple herbicide-resistant Amaranthus spp., when cover crops are integrated as a component of an IWM strategy (Loux et al 2017;Montgomery et al 2018;Wiggins et al 2015).…”
Section: Weed Control and Yield Performance Targetsmentioning
confidence: 99%
“…Recent studies have demonstrated that integrating cover crops can increase suppression of glyphosateresistant weeds, including fall-and spring-emerging horseweed [Conyza canadensis (L.) Cronquist] (Cholette et al 2018;Pittman et al 2019;Wallace et al 2019) and summer annuals Palmer amaranth (Amaranthus palmeri S. Watson) and waterhemp [Amaranthus tuberculatus (Moq.) Sauer] (Loux et al 2017;Montgomery et al 2018;Wiggins et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, recent studies have consistently demonstrated that integrating cover crops into annual grain crop rotations can improve suppression of current glyphosate-resistant weeds, including horseweed (Erigeron canadensis L.; Cholette et al 2018) and Amaranthus spp. (Loux et al 2017;Montgomery et al 2018;Wiggins et al 2016). And second, cover crops are increasingly integrated into annual grain crop rotations to provide multiple ecosystem services, including improved soil quality, maintenance of nutrient and water cycling, and enhanced biotic pest regulation (Wayman et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These programs would increase selection for resistance to postemergence herbicides and result in the possible failure of a postemergence program because of large weed sizes and high weed densities when environmental conditions are not conducive to a timely application. Residual herbicides are also recommended to be included in early postemergence applications to suppress emerging Palmer amaranth until canopy formation is achieved (Loux et al., 2017). Glufosinate, 2,4‐D, and dicamba all have excellent activity on PPO‐resistant Palmer amaranth; these programs were shown here to provide an extended period of weed control.…”
Section: Resultsmentioning
confidence: 99%